Mobilizing public support for providing needles to drug injectors: A pilot advocacy intervention - Lenton, Simon; Phillips, M. (1997)
400 members of the general public in Western Australia were surveyed regarding their attitudes to the provision of needles and syringes to drug users as a means reducing the spread of HIV. Attitudes were measured before and after the presentation of an audio-taped advocacy intervention which explained the rationale and effectiveness of needle provision. After the intervention fewer respondents agreed with stereotypical negative statements about drug injectors; and more supported needle provision, the role of pharmacists in this, and politicians taking legislative steps to support it. The impact of the advocacy intervention suggested that the public were able to assimilate information about harm reduction with injecting drug users. Providing a data based rationale resulted in an increase in support for needle and syringe provision as a public health strategy for minimising the spread of HIV.